Higher Protein Intake Does Not Augment Muscle Protein Synthetic Responses During the Early Stages of Resistance Training in Middle-Aged Adults. (7th June 2021) - Salvador, Amadeo; McKenna, Colleen; Paulussen, Kevin J.M.; Keeble, Alexander; Askow, Andrew; Scaroni, Susannah; Li, Zhong; Ulanov, Alexander; Paluska, Scott; Moore, Daniel; Burd, Nicholas
Abstract: Objectives: Dietary protein intake augments muscle protein synthesis rates during acute recovery from resistance exercise training (RET) and can help offset age-related loss in muscle mass. Skeletal muscle tissue contains a variety of different protein pools such as myofibrillar (contractile), mitochondrial (substrate oxidation), and collagen (structural support) proteins that have been reported to have different contraction and nutrient sensitivities in controlled laboratory studies. However, no study has investigated the impact of dietary protein intake on the synthesis of these specific muscle proteins fractions during RET in a free-living setting. Therefore, we investigated the effect of dietary protein intake on daily muscle protein synthesis rates (PS) within the myofibrillar (MyoPS), mitochondrial (MitoPS), and collagen (CPS) protein fractions throughout the early phase (0 – 3 wks) of RET in middle-aged adults. Methods: Twenty middle-aged adults (47 ± 1 y, BMI 28 ± 1 kg/m 2, M = 12, F = 8) were stratified and randomized to consume either moderate (MOD; 1.06 ± 0.22 g/kg/d) or high (HI; 1.55 ± 0.25 g/kg/d) amounts of protein during a dietary counseling-controlled resistance training program. On day 0, participants ingested intermittent boluses of deuterated ( 2 H) water followed by daily maintenance doses throughout the study period. Muscle biopsies were collected prior to and at weeks 1, 2, and 3 of the intervention to assess MyoPS, MitoPS, and CPS by LC/MS. Results: MitoPS decreased at 0–3 wks when compared to 0–1 wks (P = 0.010, CI: −0.77 – −0.10%/d) regardless of group (HI: 0.64 ± 0.32%/d and MOD 0.86 ± 0.55%/d; P = 0.827). A similar decline was also observed for CPS (group P = 0.323; time P = 0.007). The MyoPS in the HI condition remained constant (0–1 wk: 0.81 ± 0.42%/d and 0–3 wks: 0.81 ± 0.72%/d, P = 1.0), but MOD decreased over time (0–1 wk: 1.35 ± 0.9%/d and 0–3 wks: 0.77 ± 0.43%/d, P = 0.023). Conclusions: Our results demonstrated that additional protein intake above moderate amounts does not meaningfully potentiate the stimulation of longer-term muscle protein synthetic responses within the myofibrillar, mitochondrial, or collagen protein fractions during the early stages of a RET in middle-aged adults. Funding Sources: Funded in part by the Beef Checkoff. AFS funded by CAPES Scholarship.